Microcontroller based boost converter for vibration power harvester - Vivekanandan, Panneerselvam (2017)
A vibration Energy harvester was designed and fabricated. A proper boost converter is designed for the harvester, and then the output voltage of the boost converter is tested with several changes on the shaker parameter. The manipulating variables that were used during this project were frequency of vibration and the shaking time. The frequency used in the experiment is 4.43Hz, 5.58Hz and 6.58Hz. Whereas the time of shaking is 1minute, 2minutes, 3 minutes, 4 minutes and 5 minutes. The type of permanent magnet used is Neodymium Iron Boron. The diameter of permanent magnet used is 20mm and the thickness of the magnet is 5mm. The diameter of coil used in this project is 0.35mm, while the number of coil turn is 1000 turn. The maximum voltage3 can be achieved for the designed harvester is 1.31 V at 6.58Hz for 5 minutes. From the results it can be concluded that increasing the time of shaking and frequency can increase the voltage output further higher.